Blood pressure variability in hypertensive patients with atrial fibrillation in the VALUE trial - Maria H. Mehlum; Knut Liestøl; Torgeir B. Wyller; Tsushung A. Hua; Morten Rostrup; Eivind Berge (Blood Pressure, 2019)
Purpose: Blood pressure variability is associated with traditional cardiovascular risk factors, but little is known about the association with atrial fibrillation. We compared blood pressure variability in patients with and without atrial fibrillation using data from the Valsartan Antihypertensive Long-term Use Evaluation (VALUE) trial. Materials and methods: The VALUE trial was a randomised-controlled trial of valsartan versus amlodipine in patients with hypertension and high cardiovascular risk, followed for 4.2 years (mean). For the present analysis we included patients with electrocardiogram at baseline and during follow-up, and ≥3 visits from 6 months onwards. We compared standard deviation (SD) of all blood pressures within each visit averaged across all visits (within-visit variability) and of mean blood pressure at each visit (visit-to-visit variability) in patients with and without atrial fibrillation at baseline. We similarly compared patients who developed non-persistent or persistent atrial fibrillation during follow-up with those who did not, using t-tests, ANOVA and linear regression. Results: Of 15,245 patients in the VALUE trial, 13,827 were eligible for analysis. SD of visit-to-visit systolic blood pressure was not significantly different between patients with and without atrial fibrillation at baseline (mean difference 0.3 mm Hg, p = 0.4), but significantly higher in patients with incident non-persistent or persistent atrial fibrillation during follow-up than in those who never developed atrial fibrillation (differences 1.2 and 1.8 mm Hg, respectively, p-values <0.0001). Associations with non-persistent and persistent atrial fibrillation were confirmed in linear regression models (p-values <0.0001). SD of within-visit systolic blood pressure was not significantly different between patients with and without atrial fibrillation at baseline (p = 0.4) but significantly higher in patients with persistent atrial fibrillation during follow-up (p = 0.04). Conclusion: In patients treated for hypertension, atrial fibrillation was not associated with increased blood pressure variability, but blood pressure variability was higher in those who developed atrial fibrillation during follow-up.